Japanese Language Learning Consistency in the Digital Era - Nise Samudra Sasanti (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
This research was motivated by the pandemic which resulted in many restricted outdoor activities. The existence of restrictions on outdoor activities caused changes in behavior in the community and had an impact on reducing physical activity. Government regulations to strictly maintain health protocols as well as changing the learning system from face-to-face to virtual, affected the consistency of Japanese language learning in the digital era (new normal). This study is a qualitative descriptive study that aims to determine the consistency of Japanese language learning in the digital era (new normal) and to determine whether interest in learning Japanese has decreased or even increased in the digital era (new normal). The method used in this study is a descriptive qualitative method using a research instrument in the form of a questionnaire distributed using WhatsApp groups and e-mails. The subjects of the research were courses that held Japanese language learning. Data were obtained by distributing questionnaires, both open and closed questionnaires. The number of respondents are as many as 4 courses that open Japanese language learning online. The analyzed data shows that learning at the course remains consistent which means that the interest of Japanese language learner enthusiasts who take part in learning at the course does not change by looking at the percentage result of 100%. However, the next analyzed data got the answer that the learners increased if referring to the table of analysis results which showed a percentage of 75%.